Manipulation in the Twenty First Century English Translations of Qur’anic Verses About Jihad, Warfare, and Martyrdom - Mollanazar, Hussein; Eskandari, Muhammad (Iranian Journal of Translation Studies, 2024)
One of the best ways for people, including those wishing to convert to Islam, to get familiar with Islamic teachings is to read the translation of the Qur’an. Throughout the history, however, Qur’an translations have seen multitudinous instances of manipulations, including gross distortions of the Arabic text. The present study investigated manipulation in 76 direct, 21st-century English translations of 80 Qur’anic verses on jihad, warfare, and martyrdom, with a concentration on the translators’ religious ideology. To this end, drawing on Dukāte’s (2007) manipulation typology, an ad-hoc typology was developed. The results showed that Unmarked Complementary Addition and Attenuation were the most and the least frequently used strategies in the renditions, respectively. Furthermore, the translations by Muslim translators of different denominations exhibited significant similarity in the frequency of employing the main manipulative strategies.